2019
DOI: 10.1186/s40503-019-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Oil price, energy consumption and carbon dioxide (CO2) emissions: insight into sustainability challenges in Venezuela

Abstract: According to the Organization of Petroleum Exporting Countries (OPEC), the Bolivarian Republic of Venezuela has one of the world's largest proven crude oil reserves with 302,809 million barrels (OPEC Annual Statistical Bulletin 2018). Using average daily crude oil production for 2017 (see Fig. 1a), it would take over 390 years for Venezuela to run out of crude oil. This means that Venezuela will remain as a major crude oil producing country for a long time. Looking at the way Venezuela has managed its vast oil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…Secondly, the El Niño phenomenon has led to frequent climate disasters, which results in human deaths and huge economic losses (Ogallo, 2010;Yeh et al, 2009). The combustion of fossil energy produces carbon dioxide emissions (Ramanathan, 2006;Alkhathlan & Javid, 2015;Agbanike et al, 2019;Kashif & Nimra, 2019), which worsens the negative impact of the El Niño phenomenon. In order to protect the ecological environment and maintain sustainable development, most countries have taken measures to reduce carbon dioxide emissions and fossil energy use (e.g., the Paris Climate Conference has reached an agreement to control the carbon dioxide emissions).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the El Niño phenomenon has led to frequent climate disasters, which results in human deaths and huge economic losses (Ogallo, 2010;Yeh et al, 2009). The combustion of fossil energy produces carbon dioxide emissions (Ramanathan, 2006;Alkhathlan & Javid, 2015;Agbanike et al, 2019;Kashif & Nimra, 2019), which worsens the negative impact of the El Niño phenomenon. In order to protect the ecological environment and maintain sustainable development, most countries have taken measures to reduce carbon dioxide emissions and fossil energy use (e.g., the Paris Climate Conference has reached an agreement to control the carbon dioxide emissions).…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the increasing oil demand leads to high carbon dioxide emissions and global warming (Ramanathan, 2006;Alkhathlan & Javid, 2015;Agbanike et al, 2019;Kashif & Nimra, 2019), Collins et al (2010) prove that under the influence of global warming, the characteristics of El Niño phenomenon will probably be modified. Ciprian-Beniamin and Adrian (2012) suggest that the past and present pattern of oil consumption have negative influences on the environment and climate changes, which may cause EL Niño phenomenon.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reported that positive and negative fluctuations in crude oil prices exert influence on CO 2 emissions in the USA and China. Agbanike et al ( 2019 ) proved that CO 2 emissions exert a negative effect on economic growth in the oil-rich economy by considering a causal interaction between oil price, energy consumption, and carbon dioxide emissions in Venezuela. Mensah et al ( 2019a , b ) investigated the causal relationship with economic growth, carbon emissions, fossil fuel energy, and oil price for 22 African countries.…”
Section: Oil Price and Carbon Dioxide Emissionsmentioning
confidence: 99%
“…In this regard, [11] suggested that there was a causality interaction from oil price to energy consumption in Tunisia, while [12] found that the oil price had a significant influence on energy consumption in China. [13] tested the causal linkage between oil price and the level of carbon emissions using the ARDL model. The findings indicated that there is a positive interaction between oil prices and the level of carbon emissions in Venezuela.…”
Section: Literature Reviewmentioning
confidence: 99%